CLASSIFICATION OF GENETIC DIVERSITY FOR DROUGHT TOLERANCE IN MAIZE GENOTYPES THROUGH PRINCIPAL COMPONENT ANALYSIS - Hefny, Manal Mohamed; Ali, Abdelraheim Ahmed; Byoumi, Tarek Youssef; Al-Ashry, Mohamed; Okasha, Salah Ahmed (Journal of Agricultural Sciences (Belgrade), 2017)
Water scarcity is a universal environmental constraint for agricultural sustainability and production. Two field experiments were accomplished during growing seasons 2012 and 2013 in two sites: experimental farm of Suez Canal University, Ismailia and Romana Province, North Sinai, Egypt to evaluate 21 genotypes of maize comprising six inbred lines and their 15 F1 crosses for their drought tolerance. The experiments were arranged in split-plot with three replications, where moisture levels (100 and 50% of evapotranspiration) and maize genotypes were allocated to main and sub-plots, respectively. Results showed reduction in performance for all measure traits in response to water stress with varying degree being yield plant-1 the most decreased, inversely, proline and relative water content and anthesis-silking interval were increased. Correlation results confirmed the reduced grain yield with increasing anthesis-silking Interval, and suggested kernels row-1, relative water content, peroxidase activity and rows ear-1 in Ismailia, and rows ear-1, relative water content, peroxidase activity, kernel weight in Romana are indirect selection criteria for increasing yield under water scarcity environments. Principal component (PC) analysis showed three PCs having Eigen value >1 explained 70.67 and 70.16%; 69.79 and 71.38% of the total variability among genotypes at control and stress conditions in Ismailia and Romana, respectively. The crosses P1×P3, P4×P6, P3×P5 and P1×P5 were classified as drought tolerant under Ismailia and Romana conditions. While P1xP4, P3xP4, and P4 were considered as drought sensitive in Ismailia site, P5, P2×P4, P1×P4 and P5×P6 were the most affected by water deficiency under Romana site.